sing Chemical and Physical Mutagens for Induction of Genetic Variation in the Quantitative and Qualitative Traits of Three Cultivars of Faba beans (Vicia faba L.) - Al-Shamma, Laith Mohammed Jawad (Al-Nahrain Journal of Science, 2018)
Filed experiment was conducted to evaluate the role of chemical and physical mutagens in inducing genetic variation in the quantitative and qualitative traits, such as morphological characteristics, yield components, seed yield and protein yield of three cultivars Zaina, Aguadulce and local of Faba beans (Vicia faba L.). Nitrous acid mutagen was prepared. This acid was unstable, weakly acidic compound and decomposes rapidly that has been prepared immediately in the form of cold according to the chemical methods. Also electric shocks were used according to the physical methods, seeds were sown in the season of 2010-2011 at Research field of Biology Dept., College of Science, Baghdad Univ. Factorial Experiment was arranged in a Randomized Complete Block Design (RCBD) with three replicates. At maturity, seeds were collected first season of treatments, including the treatment comparison and then sown in the secound season of 2011-2012. Results showed that treatment of seeds soaked in nitrous acid mutagen solution for 24 hrs gave the highest seeds yield in both seasons recording 4370.39 and 3255.01 kg/ha, respectively and not significantly differed at 12-hrs soaking in the second season. Soaking treatment for 24 hrs was superior in some phenotypic traits such as plant height, leaf area index and yield components (number of branches/plant, number pods in plant, number of seeds in pod and the rate of seed weight). Also superiority in protein yield was found in the first season reached 857.87 kg / ha. The highest percentage of protein was found after using electric shock treatment for 6 or 3 min which differed significantly from seeds soaked in nitrous acid, Aguadulce and local cultivars gave higher protein percentages than Zaina cultivar in both seasons. Zaina cultivar showed superiority in seeds and protein yield in the first season reached 3774.61 and 734.4 kg / ha, respectively. While local cultivar gave the highest seeds and protein yield in the second season 3073.57 and 635.19 kg / ha, respectively. A significant interaction between cultivars and treatments was found, Zaina cultivar was superior in seeds and protein yield in the first season reaching 4997.09 and 929.94 kg / ha respectively and seed yield 3982.79 kg / ha in the second season when soaked for 12 hrs. Local cultivar gave the highest value of protein yield with mean value 755.71 kg / ha, and did not differ significantly with 3 min shocks and soaked for 24 hrs in the second season. It is concluded from this study that soaking seeds in nitrous acid mutagen solution for 24 hrs was effective in inducting genetic variation in faba bean cultivars which is useful in breeding programs either by selection or crosses.